Developing Effective Marketing Strategies for Cultural Attractions: A SWOT-Based Analysis with Educational Implications - Muhammad Saputra; Yusminar Wahyuningsih; Rizki Mufpty Pratama; Sumaria Liswita; Ilma Azizah (Al-Qalam Institue, 2025)
This study aims to identify efforts to increase tourist visits to the State Museum of Lampung Province. The research employs a qualitative descriptive approach, collecting data through interviews with museum management. The data were analyzed using SWOT analysis. Based on the SWOT matrix results, six strategies were identified for each quadrant: Strengths–Opportunities (S-O), Weaknesses–Opportunities (W-O), Strengths–Threats (S-T), and Weaknesses–Threats (W-T). The IFAS and EFAS quadrant strategy analysis showed that the X-axis score was 0.37 and the Y-axis score was 0.15, both in the positive range. This positioning indicates that the appropriate marketing strategy for the museum falls into Quadrant I, which suggests the application of an aggressive strategy. The implications of this study for educational management suggest that applying an aggressive marketing strategy can enhance engagement and attract more visitors to cultural institutions. By utilizing a SWOT analysis, education managers can identify key strengths and opportunities, enabling them to develop targeted strategies that enhance institutional visibility, accessibility, and overall effectiveness in attracting diverse audiences.